Lara Jean’s Anxiety in To All the Boys I’ve Loved Before - Juliananda, Kamila Rosa; Furaida, Asni (Journal of Literature, Linguistics, & Cultural Studies, 2024)
The research explores the theme of anxiety in the novel To All the Boys I've Loved Before by Jenny Han, focusing on the main character, Lara Jean. Anxiety has a significant impact on adolescents during the transition from childhood to adulthood. This study investigates Lara Jean's condition of experiencing anxiety and aims to answer questions about the types and causes of her anxiety experiences. This research uses a literary criticism approach by applying Sigmund Freud's anxiety theory to analyze the novel To All The Boys I've Loved Before by Jenny Han. It explores the types of anxiety and their causes experienced by the main character, Lara Jean. Data collection includes close reading, recording relevant information, and sorting data to answer research questions. The findings in this research are Lara Jean's experiences of reality anxiety, neurotic anxiety, and moral anxiety. Reality angst sets in when her secret box disappears, and her secret is discovered, leading to tension with her sister Margot and attempts to avoid Josh. Neurotic anxiety revolves around fear of punishment for impulsive actions, including concerns about Josh revealing love letters and potential bullying from Peter's ex, Genevieve. Moral anxiety is related to the violation of decency norms triggered by Lara Jean's controversial video and the conflict with family values. This study identified threat, conflict, and frustration as essential factors contributing to Lara Jean's anxiety, providing insight into the complex interactions between external pressures and internal conflict in her life.